The Impact of Professional Skepticism, Competence, and Independence on Audit Quality During the Covid-19 Pandemic - Perdana, ST K Caraka Vidi; Muchayatin, Muchayatin (Untag Business and Accounting Review, 2023)
This research is empirical research that aims to analyze the influence of professional skepticism, competence, and independence on audit quality during the COVID-19 pandemic. The population studied was 81 staff at the Leonard, Mulia, and Richard Semarang Public Accounting Firm. The sampling technique used is saturated. The data used is primary data obtained by distributing questionnaires to audit staff and 77 questionnaires could be processed. The data technique used in this research is multiple linear regression. The results show that professional skepticism, competence, and independence have a positive effect on audit quality during the COVID-19 pandemic. The implication are auditors should not delay decisions, should stick to the applicable Financial Accounting Standards regulations, and maintain an independent attitude in carrying out the audit process.